FEATURES OF ANXIETY-DEPRESSIVE MANIFESTATIONS AND THEIR RELATIONSHIP WITH THE SUBJECTIVE WELL-BEING OF MOTHERS RAISING CHILDREN WITH ORGANIC NERVOUS SYSTEM DISORDERS (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. The birth and upbringing of a child with a developmental disorder is a traumatic factor that leads to changes in the personality of parents and their lives in general. Parents may experience increased anxiety, depression, chronic sadness, apathy, hopelessness, "emotional burnout," etc. The article presents the results of a theoretical and empirical study of the anxiety-depressive characteristics of parents raising children with organic damage to the nervous system. Theoretical material on the psychological characteristics of parents raising children with developmental disorders is presented. The results of the study include a comparison of the level of anxiety and the presence and severity of depression in mothers raising a child with organic damage to the nervous system with those raising normotypical children. A correlation between the components of subjective well-being and indicators of anxiety and depression has been revealed.Methods. In the process of the study, theoretical and methodological analysis, testing using the scale for assessing generalized anxiety disorder (GAD-7), the Patient Health Questionnaire (PHQ-9) for assessing depression severity, and the short multidimensional well-being questionnaire "PERMA-PROFILER" (adapted by Savchenko O.V. and Lavrynenko D.G.) were used. Statistical analysis was conducted using the Jamovi 2.3.28 software.Results. The study made it possible to determine the level of anxiety and the presence and severity of depression in mothers raising normotypical children and children with developmental disorders. The level of anxiety in mothers raising children with organic lesions of the nervous system is significantly higher than in those raising normotypical children—this was true across all levels of anxiety (minimal, mild, moderate, severe). Half of the control group does not experience depression, while only a third of the experimental group is depression-free. Rates of mild, moderate, and moderately severe depression are higher in mothers raising children with organic nervous system damage. The percentage of respondents with severe depression is similar in both groups. Correlations were found between depression and subjective well-being components (positive emotions, relationships, meaning, health, engagement, and negative emotions), as well as between anxiety and components such as positive emotions, relationships, meaning, and negative emotions.Conclusions. Based on the analysis of the research data, the initial hypothesis regarding the low level of subjective well-being in mothers raising children with organic nervous system damage is confirmed. This conclusion supports the continuation of data collection for further research.
Keywords: anxiety; depression; child with developmental disabilities; emotional and crisis states; normotypical children